Combined effects of oxygen pressures and RF powers on the electrical characteristics of ITO-based multilayer transparent electrodes. (November 2019) - Im, Hyeong-Seop; Kim, Su-Kyung; Lee, Tae-Ju; Seong, Tae-Yeon
Abstract: The opto-electrical properties of plasma-treated ITO films were investigated as functions of oxygen pressures (3.33 and 26.66 Pa) and radio-frequency (RF) plasma powers (50 and 150 W). The plasma-treated samples showed higher transmittance than the untreated sample. After the low-oxygen treatment, the carrier concentration increased with increasing plasma RF power and the figure of merit (FOM) also increased from 1.17 × 10 −3 to 1.65 × 10 −3  Ω −1 . This was not the case for the high-oxygen treatment. The ITO surfaces became smoother with increasing RF power. It was shown that unlike the high-oxygen treated samples, the In 3 d and Sn 3 d core levels for the low-oxygen-treated ITO films were shifted to higher energies compared to that of the untreated sample. ITO films of ITO/Ag/ITO multilayers (IAI) were plasma-treated at different conditions. Their transmittance maxima were in the range of 91.58–92.32% at 492–501 nm. The bottom-ITO-treated sample gave 23.1% higher mobility and 19% lower sheet resistance than the untreated IAI. The wetting characteristics of deionized (DI) water on the ITO films showed that the surface energy of ITO films increased from 34.22 to 71.14 mJ/m 2 when the oxygen pressures increased from 0 to 26.66 Pa. Graphical abstract: Image 1 Highlights: First investigate the combined effects of oxygen pressures and RF powers on the performance of ITO. Plasma-treated sample shows higher overall transmittance than the untreated sample. The bottom-ITO-treated sample gave 19% lower sheet resistance than the untreated one. The work function of ITO controlled by adjusting the oxygen pressures and RF powers. Plasma-treated ITO can serve as not onlyanode but alsocathode for solar cells or OLEDs.